Distribution patterns and evolution of antimicrobial resistance in Gram-negative bacteria within the intensive care unit of a tertiary hospital from 2019 to 2024 - Chen, Xiaoying; Liu, Xin; Ren, Wenyan; Li, Hongyan; Yang, Siyun (Frontiers in Microbiology, 2025)
BackgroundThis study aims to investigate the distribution and drug resistance of Gram-negative bacteria in the intensive care unit (ICU) of a tertiary general hospital in Sichuan Province, with the goal of promoting rational antibiotic use and reducing multidrug resistance.MethodsA retrospective analysis was conducted on the distribution and drug resistance of Gram-negative bacteria in ICU samples collected from January 2019 to December 2024.ResultsA total of 83,944 culture samples were analyzed, primarily blood (45.27%) and sputum (41.34%) specimens, with a steady increase in sample types annually. A total of 7,211 strains were isolated, 76.43% of which were from respiratory tract specimens. The predominant pathogens included Klebsiella pneumoniae (31.17%), Acinetobacter baumannii (30.11%), Escherichia coli (14.05%), and Pseudomonas aeruginosa (11.34%). The detection rates for carbapenem-resistant A. baumannii (CRAB) were 61.88%, carbapenem-resistant K. pneumoniae (CRKP) 29.28%, carbapenem-resistant P. aeruginosa (CRPA) 5.80%, and carbapenem-resistant E. coli (CREC) 3.04%. Susceptibility testing revealed fluctuating resistance rates for E. coli over the past 6 years. Notably, K. pneumoniae exhibited significant resistance to carbapenems (e.g., imipenem) and third-generation cephalosporins (e.g., ceftazidime).ConclusionFrom 2019 to 2024, the ICU experienced a severe problem with Gram-negative drug-resistant bacteria, particularly Enterobacteriaceae resistant to third-generation cephalosporins. A. baumannii isolates demonstrated resistance to most antibiotics, underscoring the need for continuous monitoring and the selection of effective antibiotics based on clinical practice.